Ação de um composto de origem mineral na sobrevivência e fecundidade do percevejo-marrom-da-soja (Euschistus heros Fabr.) (Hemiptera: Pentatomidae) - Silva, Mayara Fabiana da (2018)
The cultivation of soybeans occupies a large area of land in Brazil, but pest attack, despite all the technology already developed, especially in relation to chemical insecticides, remains a determining factor for the success of the crop, since such substances, when bad used as a single tactic, become inefficient and pose a danger to the environment and health. In this context, the objective of this work was to verify the use of a compound of mineral origin in the control of E. heros, the main pest of the soybean crop, as an alternative to the conventional method. To this end, suspensions of 0, 4, 8 and 16% of the FertP® product in aqueous suspension were prepared along with 0.01% Tween, which were sprayed onto E. heros eggs up to 24 hours old. The incubation period and number of hatched insects were evaluated. First-instar nymphs, recently hatched, were also submitted to spraying, evaluating the mortality and duration of the instar. To verify the longevity and reproductive capacity of adults, couples with up to 48h of ecdise were immersed in suspensions and transferred to cages, being evaluated daily for 32 days regarding longevity, number of eggs and eggs viability. After compiling and analyzing the collected data, it was concluded that the product under study did not present any significant effect on any of the biological parameters of the soya-brown bug